2020
DOI: 10.1038/s41398-020-00966-4
|View full text |Cite
|
Sign up to set email alerts
|

Integration of postmortem amygdala expression profiling, GWAS, and functional cell culture assays: neuroticism-associated synaptic vesicle glycoprotein 2A (SV2A) gene is regulated by miR-133a and miR-218

Abstract: Recent genome-wide studies have begun to identify gene variants, expression profiles, and regulators associated with neuroticism, anxiety disorders, and depression. We conducted a set of experimental cell culture studies of gene regulation by micro RNAs (miRNAs), based on genome-wide transcriptome, proteome, and miRNA expression data from twenty postmortem samples of lateral amygdala from donors with known neuroticism scores. Using Ingenuity Pathway Analysis and TargetScan, we identified a list of mRNA-protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 78 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…However, microRNAs in non-cortical regions are also likely to contribute to PFC development and to the etiology of MDD, schizophrenia and substance use disorders. Indeed, miR-218 levels have been shown to be also elevated in the postmortem lateral amygdala of individuals with neuroticism and anxiety [138]. In rodents, the disruption of PFC dopamine development by exposure to recreational-like doses of stimulant drugs of abuse in adolescence requires miR-218 upregulation in the ventral tegmental area [139].…”
Section: Discussionmentioning
confidence: 99%
“…However, microRNAs in non-cortical regions are also likely to contribute to PFC development and to the etiology of MDD, schizophrenia and substance use disorders. Indeed, miR-218 levels have been shown to be also elevated in the postmortem lateral amygdala of individuals with neuroticism and anxiety [138]. In rodents, the disruption of PFC dopamine development by exposure to recreational-like doses of stimulant drugs of abuse in adolescence requires miR-218 upregulation in the ventral tegmental area [139].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR-218 has been suggested to show abnormal expression in a variety of neurodegenerative and neuropsychiatric disorders, including Alzheimer's disease, Parkinson's disease, schizophrenia, depression, and anxiety (19)(20)(21)(22)(23)(24). miR-218 includes miR-218-1 and miR-218-2, which are located in the introns of the tumor suppressor genes SLIT2 and SLIT3, respectively (25).…”
mentioning
confidence: 99%
“…The results indicated that miR-133a and miR-128 in the amygdala generated the same expression pattern and translation inhibition function with regard to synaptic vesicle glycoprotein 2A (SV2A) regulation. Cell experiments also confirmed that miR-133a and miR-128 targeted Sv2A 3 UTR to inhibit its expression [60]. Another study on the LPS-induced model showed that miR-96 was targeted and negatively regulated SV2C expression in the hippocampal CA1 region, decreased 5-hydroxyindole acetic acid (5-HT) and dopamine (DA) release, and induced the development of depres-sion [61].…”
Section: Mirnas and Neurotransmission-related Receptorsmentioning
confidence: 81%